2003
DOI: 10.1002/cncr.11725
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of matrix metalloproteinase‐2 and tissue inhibitor of metalloproteinase‐2 is correlated with poor prognostic variables in patients with thymic epithelial tumors

Abstract: BACKGROUND A distinction between noninvasive, invasive, and metastatic thymoma on the basis of the cytologic features is difficult. The current study investigated whether the expression of MMP and TIMP was correlated with tumor invasiveness and prognosis in patients with thymoma. METHODS Tumor tissue samples were obtained from 42 patients with thymic epithelial tumors between 1974 and 2001 at Tokushima University Hospital. Three‐micrometer‐thick, formalin‐fixed, paraffin‐embedded tissue sections were immunosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…11 An immunohistochemical reaction for TIMP-2 was also observed in the basal cell hyperplasia or squamous metaplasia. 11 Sogawa et al 13 reported that immunostained TIMP-2 expression levels were very low in patients with noninvasive thymic epithelial tumors, but very high in those with invasive tumors. Therefore, we considered that SCC contained more of an epithelium component than adenocarcinoma, resulting in greater overexpression of TIMP-2.…”
Section: Discussionmentioning
confidence: 98%
“…11 An immunohistochemical reaction for TIMP-2 was also observed in the basal cell hyperplasia or squamous metaplasia. 11 Sogawa et al 13 reported that immunostained TIMP-2 expression levels were very low in patients with noninvasive thymic epithelial tumors, but very high in those with invasive tumors. Therefore, we considered that SCC contained more of an epithelium component than adenocarcinoma, resulting in greater overexpression of TIMP-2.…”
Section: Discussionmentioning
confidence: 98%
“…Matrix metalloproteinase and tissue inhibitor of metalloproteinase were suggested to be involved in invasiveness. 36,37 Comparisons of gene expression between early and late stages by DNA microarray analysis revealed differences in c-Jun and AL050002 (unknown gene), and these genes were expressed in type B3 at a higher level than in type AB, B1, and B2 thymomas. 38 Results from the analysis of chromosomal imbalances are compatible with the indolent behavior of type A and AB thymomas and the aggressive nature of type B3.…”
Section: Correlation Of Who Histological Classifi Cation With Geneticmentioning
confidence: 98%
“…As distinguishing between non-invasive, invasive, and metastatic thymomas on the basis of the cytologic features is difficult, several studies have assessed factors associated with the invasiveness of thymoma [3,[6][7][8][9][10][11]; however, few studies have addressed the genetic alterations that occur in the tumourigenesis of thymoma [10,[12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing non-invasive, invasive, and metastatic thymomas on the basis of their cytologic features is difficult; however, thymic carcinoma and thymoma can be distinguished histologically in most cases [1,2,4,5]. Several studies have assessed factors associated with the invasiveness of thymoma, such as the nuclear areas of epithelial cells, the nuclear DNA content, proliferative activity (proliferating cell nuclear antigen, Ki-67, mitotic figures), the argyrophilic nucleolar organizer region, p53 expression and metalloproteinases [6][7][8][9][10][11]; however, few studies have addressed the genetic alterations that occur in the tumourigenesis of thymoma [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%